2018
DOI: 10.15562/jdmfs.v3i2.770
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dominant aerob bacteri in saliva of the patient with fixed ortodontic appliance

Abstract: Objective: To understand the kind of dominant aerobic bacteria in patient's saliva with an orthodontic appliance. Material and Methods: This is a descriptive observational study with cross-sectional design. Saliva samples from as many as 16 patients with fixed orthodontic appliances were collected. Saliva was taken by a swab method using wood a cotton swab, then put into tube filled with stuart medium. The samples was then isolated to blood agar, put into incubator for 24 hours and then assessed for the catala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The lowest amount of nickel and chromium in both periods was released from NiTi and HANT archwires, respectively nickel ion release decreased over time while the chromium release increased. [14][15][16] A various study reported a release of 20 μg of nickel per day from a simulated full mouth orthodontic appliance. In this study, the total release of nickel values was well below the normal daily intake of Ni 200-300 μg/day.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest amount of nickel and chromium in both periods was released from NiTi and HANT archwires, respectively nickel ion release decreased over time while the chromium release increased. [14][15][16] A various study reported a release of 20 μg of nickel per day from a simulated full mouth orthodontic appliance. In this study, the total release of nickel values was well below the normal daily intake of Ni 200-300 μg/day.…”
Section: Discussionmentioning
confidence: 99%